"Switzerland of Arabia": Omani Foreign Policy and Mediation Efforts in the Middle East. Issue 4 (2nd October 2021) - Worrall, James
ABSTRACT: In recent years, Oman has been recognised as a key mediator in the Gulf and the wider Middle East. The successful completion of the 2015 Iran nuclear deal, in particular, firmly cemented its reputation as a peacemaker. To fully understand Omani mediation practices in the region, Muscat's mediation must be placed within the context of the Sultanate's wider foreign policy, and all known mediations must be assembled in one place in order to develop a typology to better understand forms and patterns. Ultimately, mediation both serves and is enabled by the Sultanate's foreign policy. This was not an inevitable outcome. Over the course of Qaboos' reign, Oman has developed into an 'Interlocutor State', in which the practice of mediation has become an important tool in furthering the central goals of preserving Oman's independent foreign policy, and thus ultimately the Sultanate's sovereignty and security itself.